The development of an application for recording the paths of school vehicles - Bin-ahmad, Habib; Mansattha, Muhammad (Princess of Naradhiwas University Journal, 2019)
Every weekday, millions of students must travel between home and school, using road transportation. In Thailand as we know, road statistics are extremely alarming. Too many die or get injured. Some students use boarding school vehicles, while others use a personal car with (or without) an adjustable seat. But most of them are simply passengers in a van. This research is based on the belief that school vehicle drivers will drive more carefully if they are tracked. So it proposes a speed and location tracking mobile application that would record routes of school vehicles and send On-Board Diagnostics (OBD) data, using the OBD II system, sending data to a server that records and retrieves useful information such as driving speed and route positioning. Since school vehicle accidents have happened way too often in the past, with such a system we would at least understand the circumstances and the cause of each accident. From the experiment, we could obtain precise road records every 10 seconds. Data showed that tracking information can be used as a reference to determine driving speed with reliability and, hopefully, save lives of students and their drivers, by increasing road safety.